Identification of Candida spp. in the oral cavity in patients with malignant diseases - Glažar, Irena; Prpić, Jelena; Muhvić Urek, Miranda; Pezelj-Ribarić, Sonja (Vojnosanitetski pregled, 2017)
Background/Aim. Oral candidiasis frequently causes discomfort in patients treated for malignant diseases, acting as well as a potential source of systemic infection. This disease may present itself through different clinical manifestations of both acute or chronic type. The aim of this study was to identify different Candida species from oral cavities of patients suffering from malignant diseases. Methods. Thirty patients admitted to the hospital for diagnostics/treatment of malignant diseases were included in this investigation. All subjects had visible changes of oral mucosa in the form of pseudomembranes and inflammation corresponding to oral candidiasis. Control group included 30 non-hospitalized patients diagnosed with candidiasis. Diagnosis of oral candidiasis was confirmed in all patients by microbiological analysis of tongue swabs. For microbiota identification, three different tests were used: germination test, fungal growth test on corn meal agar, and biochemical identification with commercially available ID 32 C kit (bio-Merieux, Marcy-l´Etoile, France). Results. Out of 30 isolates collected from hospitalized patients, 90% was related to Candida albicans, 7% was identified as Candida kefyr, and 3% as Candida famata. In samples collected from non-hospitalized controls, we isolated Candida albicans in 90% of the cases, in 7% Candida kefyr, while in 3% we identified Candida glabrata. Conclusion. Based on this investigation, oral candidiasis in patients treated with radiotherapy and chemotherapy is mainly caused by Candida albicans. It is to be expected that Candida albicans will remain the most significant causative agent of oral candidasis, although we must bear in mind the possibility of other pathogenic species.